Rancang Bangun Media Pembelajaran Tenses English Berbasis Android menggunakan Algoritma Fisher-Yates - Vebiant, Kiki; Wahyuddin, M Iwan; Komala Sari, Ratih Titi (KITA Institut, 2021)
English is a language that is widely used in various countries in the world. This makes english an international language and also must be studied in schools or even universities. In english, the verb used will be different at different times, places, and also events or it can be called a change in the verb (tense). So, learning and mastering tenses in english is the basis for learning or mastering english. This study aims to design and build an Android-based learning media for english tenses. The design applies a form of english tense quiz using the Fisher-Yates algorithm, which is a randomization algorithm that can randomize the order of the quiz questions so that the order of the quiz questions is not always the same and there are no repeated quizzes. The expected results will later become a learning medium for people who want to learn or master english and can understand the tenses in english.Keywords:Android, Fisher-Yates, Tenses, Learning Application.